Calcaneocuboid and Naviculocuneiform Dislocation: An Unusual Injury of the Midfoot. (28th September 2020) - Kummer, Anne; Crevoisier, Xavier; Eudier, Antoine
Abstract : Introduction . Midfoot dislocations are rare traumatic injuries. The best known patterns involve the Lisfranc and Chopart joints, although some other types have been described. Dislocations that occur at the level of the naviculocuneiform and calcaneocuboid joints simultaneously represent a very rare configuration of dislocation. Case Presentation . A 34-year-old man sustained a crush injury to his left foot causing a complete dislocation through the naviculocuneiform and calcaneocuboid joints. Immediate closed reduction and percutaneous pinning were performed, followed by open reduction and stabilization of both joints two weeks later. Anatomical reduction was obtained, and the clinical outcome remained satisfactory 10 months after surgery. Discussion . Anatomical reduction is essential to obtain favorable outcomes in traumatic midfoot injuries. An unusual pattern of midfoot dislocation can be treated according to the same principles as those for classical Lisfranc or Chopart injuries.